(untitled) (Zaporizhzhia Historical Review, 2021)
The system of Cossacks military ranks after 1775 is being investigated. It is shown that the documents of Azov province chancellery illustrate and deepen the knowledge of Russian government and local administratives’ intention to unify the military ranks of Cossacks as a part of politics directed at the unification of administrative and political organization of Southern Ukrainian region and therefore at the liquidation of Cossack class.